How the death of a father/husband affects the mother-child rela[t]tionship - Brite, Brooke M (Kansas State University, 2008)
Throughout this report, I focused on how the mother-child relationship is affected following the loss of a husband/father. I started with a case study and followed with the effects of losing a spouse, the effects of losing a parent, specifically how the mother-child relationship is impacted, and ended with a recommendation for a course of therapy, referencing back to the case study presented in the opening chapter. The loss of a husband/father is an extremely difficult occurrence, and as illustrated in this report, will have a lasting impact on the complexities of the mother-child relationship.
Keywords: mother-child relationship; grief; death of father; Psychology, Social (0451); Social Work (0452); Sociology, Individual and Family Studies (0628)